Synthesis and characterization of benzene-1.3.5- tricarboxamide organogel-gold nanoparticles composite - Aervina Misron, 1993-, author; Mustaffa Shamsuddin; Fakulti Sains (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2016)
Project Paper (Sarjana Muda Sains (Kimia)) - Universiti Teknologi Malaysia, 2016